Systematic review of clinical manifestations, management and outcome following accidental ingestion of liquid mosquito repellent vaporiser in children - Babar Naeem; Aqdas Arshad; Junaid Saleem; Agha Syed Ali Haider Naqvi; Sidra Kausar; Kantash Kumar; Aashar Khalid; Parkash Kumar (BMJ Publishing Group, 2024)
Background Pyrethroid-based mosquito repellents are widely used to control mosquito-borne diseases. Liquid mosquito-repellent vaporisers are effective modes of pyrethroid delivery but can also pose significant health risks if ingested or used improperly.Objective This systematic review was performed to assess the demographic distribution, clinical presentation, management strategies and outcomes in children resulting from accidental ingestion of liquid mosquito repellent vaporiser.Methods The study adheres to the reporting standards outlined in the PRISMA Statement for Systematic Reviews and was prospectively registered with PROSPERO (record # CRD42023413937) to enhance transparency and minimise reporting bias. A comprehensive search was conducted on PubMed, Scopus and Google Scholar using specific MeSH terms related to insecticides, mosquito repellents, pyrethroids, ingestion, poisoning, toxicity and prevention. The reference lists of the included studies were also reviewed for additional relevant articles. The inclusion criteria involved studies published in peer-reviewed journals between 2000 and 2023 that focused on children under 18 years old with a history of mosquito-repellent ingestion based on primary data.Results Twelve studies met the inclusion criteria; these were primarily case reports from India, China and the UAE. Male children were predominantly affected, and symptoms included vomiting, convulsions, cough and respiratory distress. Management primarily involved supportive and symptomatic measures, including atropine for salivation and antiepileptic drugs for seizures. Respiratory support was provided for respiratory complications.Conclusion Despite the known risks and diverse presentations of pyrethroid poisoning caused by liquid mosquito repellent vaporiser in children, the limited substantial evidence in the literature underscores the urgent need for comprehensive research to refine management approaches and enhance preventive measures.